2002
DOI: 10.1021/es0155534
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and Efflux of Cd and Zn by the Green Mussel Perna viridis after Metal Preexposure

Abstract: Cadmium and zinc uptake from the dissolved phase, assimilation efficiency from the dietary phase, efflux rate constants, and body burden as well as clearance rate were measured in the green mussel Perna viridis with or without laboratory preexposure to Cd or Zn. Efflux rate constants and clearance rates were little affected by preexposure to either Cd or Zn. In contrast, the assimilation of Cd increased by 1.2-1.6 in mussels preexposed to Cd (subsequent Cd concentrations 10.2-25.9 microg(-1)) as compared to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
121
4
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 106 publications
(137 citation statements)
references
References 39 publications
11
121
4
1
Order By: Relevance
“…Tissue Ag concentration and subcellular Ag distribution. Total tissue Ag concentrations in the green mussels were analysed in 5 individuals from each site, using previously described methods (Blackmore & Wang 2002, Ng & Wang 2004. The soft tissue of the mussels was acid-digested, and the digests were analysed by inductively coupled plasma-mass spectroscopy (ICP-MS, Perkin-Elmer, Elan 6000).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tissue Ag concentration and subcellular Ag distribution. Total tissue Ag concentrations in the green mussels were analysed in 5 individuals from each site, using previously described methods (Blackmore & Wang 2002, Ng & Wang 2004. The soft tissue of the mussels was acid-digested, and the digests were analysed by inductively coupled plasma-mass spectroscopy (ICP-MS, Perkin-Elmer, Elan 6000).…”
Section: Methodsmentioning
confidence: 99%
“…The clearance rate was used to compare any physiological difference in pumping activities between the 2 populations of mussels, and was quantified using a wellestablished method (Blackmore & Wang 2002, Shi et al 2003). The clearance rates of 8 individuals were determined, and the rate of each individual was calculated from the mean of 2 consecutive measurements (0 to 20 and 20 to 40 min).…”
Section: Methodsmentioning
confidence: 99%
“…This could be ascribed to a lower water-filtering rate by the animal exposed to such high amounts of contaminants; however, an interaction between the metals or a competition during their cellular uptake could be another possible explanation for the reduced effect of Cd. In Perna viridis, for example, the preexposure to Zn has a negative effect on Cd assimilation and potentially reduces Cd uptake (Blackmore and Wang 2002); Meshitsuka et al (1987) reported that cadmium uptake is inhibited by Cu(II) and affected by Zn(II) in cultured cells.…”
Section: Figmentioning
confidence: 99%
“…A strong positive association between concentrations of Zn and Cd in crabs implied that the Cd and Zn originated from a common source. Blackmore and Wang (2002) found the same results in green mussels [39]. Positive relationships between the Cd and Zn in water and sediment implied that Cd and Zn had common sources in water and sediment.…”
Section: Discussionmentioning
confidence: 65%